A diagnostic accuracy study comparing RNA LAMP, direct LAMP, and rapid antigen testing from nasopharyngeal swabs - Cao, Guojun; Lin, Ke; Ai, Jingwen; Cai, Jianpeng; Zhang, Haocheng; Yu, Yiqi; Liu, Qihui; Zhang, Xinyun; Zhang, Yi; Fu, Zhangfan; Song, Jieyu; Wang, Hongyu; et al. (Frontiers in Microbiology, 2022)
Introduction During the coronavirus disease 2019 (COVID-19) pandemic, the early detection and isolation of individuals infected with severe acute respiratory syndrome coronavirus disease 2 (SARS-CoV-2) through mass testing can effectively prevent disease transmission. SARS-CoV-2 nucleic acid rapid detection based on loop-mediated isothermal amplification (LAMP) may be appropriate to include in testing procedures. Methods We used 860 nasopharyngeal specimens from healthcare workers of Huashan Hospital and COVID-19 patients collected from April 7th to 21st, 2022, to assess the clinical diagnostic performance of the LAMP assay marketed by Shanghai GeneSc Biotech and compared it to the result of a rapid antigen test (RAT) head-to-head. Results Overall, the diagnostic performance of LAMP assay and RAT were as follows. The LAMP assay represented higher sensitivity and specificity than RAT, especially in the extracted RNA samples. The sensitivity was 70.92% and 92.91% for direct LAMP and RNA-LAMP assay, respectively, while the specificity was 99.86% and 98.33%. The LAMP assay had overall better diagnostic performance on the specimens with relatively lower Ct values or collected in the early phase (≤7 days) of COVID-19. The combination of LAMP assay and RAT improved diagnostic efficiency, providing new strategies for rapidly detecting SARS-CoV-2. Conclusion The LAMP assay are suitable for mass screenings of SARS-CoV-2 infections in the general population.